Habitação de interesse social na produção do habitat rural em territórios de reforma agrária no oeste do estado de São Paulo, Brasil - Angel Stive Castañeda Rodriguez; Akemi Ino (Cidades, Comunidades e Território)
In the theoretical and practical field applied to land use planning, the rural has been associated with a generic conception of empty, useless space or as residue of the different real estate processes. In this way, the production of the rural habitat is almost always reduced to partial, discontinuous measures and clearly dependent in political and economic terms on the urban dimension. This article presents some results of a research carried out in three agrarian reform settlements in the state of São Paulo, a territory characterized by the intensification of the struggle for land and its precarious conditions, marked by the lack of infrastructure, services, support for production and housing. In other words, peasants who permanently face two struggles: initially, they fight to occupy the land and later they fight to remain on it. We intend to demonstrate the relevance of social housing in the production of rural habitat in Brazilian agrarian reform territories, based on the processes and contradictions inherent to its implementation. From a theoretical-methodological point of view, this work points out that the critical construction is carried out from the object, supported by categories of analysis complementary to the study in the field. It becomes essential to situate the question of rural social housing at another level of reflection, understood as a ‘socio-spatial phenomenon’, which simultaneously integrates the production of built environments, the question of land, technological and productive processes, work and effective participation of the community.